LEKSIKON PERSAWAHAN DI KOTA PADANG - sonezza ladyanna; Rona Almos; Herry Nur Hidayat; Seswita Seswita (Puitika, 2018)
Rice fields in urban areas are getting narrower and made rice field activities are decreasing which of course will result in the reduced use of lexicons in this field. Therefore, it is needed to conduct a reseach on the lexicon of rice fields in Padang city. This article discusses the lexicons of rice fields used by people in Padang. This research is conducted qualitatively. Data is collected by referring method and analyzed by referential equivalent method. Then, it is presented in an informal method. From the results of the analysis, it can be concluded that the rice lexicons found can be grouped into four, namely process lexicons, tools, flora, and fauna which are, mambajak , manyiang, manyikek, mananam,, etc. This lexicon must be inventoried so that the lexicon inheritance can be carried out as the local wisdom of the lexicon can be maintained for the next generation. Key words: Lexicons, rice-fields, Padang